Diskursus Harmoni Desa Pancasila Balun - Farokhah, Fiqih Aisyatul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This study examines the discourse of harmony of Pancasila Balun Lamongan Village as a strengthening of Islamic moderation values through local wisdom that focuses on its representation in online media. In the era of Industrial Revolution 4.0, the influence of online media is becoming increasingly pronounced relative to print media. This research examines the values of Islamic moderation constructed and promoted through online media narratives and, secondly, the forms of local wisdom in Balun Village that play an essential role in maintaining interfaith harmony. This research analyses the lenses of cultural studies and discourse theory to investigate the role of online media in shaping discourses on tolerance, pluralism, and culture. The findings indicate that the discourse constructed seeks to influence public perceptions of Balun Village yet also functions as a hegemonic instrument that underscores the prevailing values of Islamic moderation. Thus, the discourse plays a role in influencing public perceptions and promoting Islamic moderation.